Prenatal diagnosis and molecular characterization of PKHD1 variants in two Chinese fetuses with Caroli disease/syndrome - Huang, Hui; Zhao, Sheng; Wang, Dan; Pan, Shengbao; Liu, Fang; Chen, Peiwen; Chen, Xinlin (Frontiers in Genetics, 2025)
BackgroundCaroli disease (CD) and Caroli syndrome (CS) are rare inherited disorders characterized by dilatation of intrahepatic bile ducts, caused by PKHD1 pathogenic variants. Prenatal diagnosis of CD or CS is extremely rare, with only two cases having genetic analysis worldwide. In this study, we describe the prenatal imaging and genetic findings in two Chinese fetuses with CD/CS.MethodsPrenatal ultrasound and magnetic resonance imaging (MRI) findings were collected for both fetuses. Whole exome sequencing was performed in family 1 and fetus 2, using fetal umbilical cord and parental peripheral blood. The candidate variants were validated using Sanger sequencing. The effect of the splice site variant was evaluated by in vitro minigene assays with the pcMINI-C and pcMINI vectors.ResultsBoth fetuses presented with multiple dilated intrahepatic bile ducts and features consistent with autosomal recessive polycystic kidney disease (ARPKD) on ultrasound and MRI at 33 weeks (Fetus 1) and 39 weeks (Fetus 2) gestation; Fetus 2 also exhibited oligohydramnios. Trio WES analysis revealed two compound heterozygous variants of PKHD1, a missense variant c.7912T>A (p.Tyr2638Asn) and an intronic splice-site variant c.3364 + 3A>T, in Fetus 1, with the father carrying c.7912T>A and the mother c.3364 + 3A>T. WES analysis in Fetus 2 identified two PKHD1 candidate variants, c.9901G>T (p.Glu3301Ter) and c.2507T>C (p.Val836Ala). These variants were confirmed by Sanger sequencing, and in silico prediction and conservation analysis suggested their potential pathogenicity. The c.3364 + 3A>T variant has been previously reported postnatally but functionally uncharacterized. In vitro minigene assays demonstrated that it caused exon 29 skipping, leading to a frameshift and a premature stop codon (c.3229_3364del p.Gly1077Alafs*12).ConclusionWe reported the first prenatally diagnosed CD/CS cases with genetic analysis in the Chinese population, and experimentally validated the pathogenicity of the recurrent splice site variant c.3364 + 3A>T by a minigene assay. Our findings broaden the PKHD1 variation spectrum in these rare cases and recommend including prenatal cases to refine the reported genotype-phenotype correlations. We also emphasize the need of WES in probands with CD or CS for early molecular diagnosis in subsequent pregnancies.